2017
DOI: 10.18632/oncotarget.18101
|View full text |Cite
|
Sign up to set email alerts
|

Formation, function, and exhaustion of notochordal cytoplasmic vacuoles within intervertebral disc: current understanding and speculation

Abstract: Notochord nucleus pulposus cells are characteristic of containing abundant and giant cytoplasmic vacuoles. This review explores the embryonic formation, biological function, and postnatal exhaustion of notochord vacuoles, aiming to characterize the signal network transforming the vacuolated nucleus pulposus cells into the vacuole-less chondrocytic cells. Embryonically, the cytoplasmic vacuoles within vertebrate notochord originate from an evolutionarily conserved vacuolation process during neurulation, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 98 publications
1
28
0
Order By: Relevance
“…When the bony vertebra is formed, hyaline cartilage adjacent to the IVD is maintained and develops to the CEP at the end plate ( Figure 1). In the early stage of human life, the NP is populated by clusters of large, vacuolated notochordal cells and by small chondrocyte-like cells [13]. However, by the second decade of life, the notochordal cells in the NP disappear, and the NP transitions from a notochordal structure to a tissue embedded with small chondrocyte-like cells [14].…”
Section: The Development Of the Ivdmentioning
confidence: 99%
“…When the bony vertebra is formed, hyaline cartilage adjacent to the IVD is maintained and develops to the CEP at the end plate ( Figure 1). In the early stage of human life, the NP is populated by clusters of large, vacuolated notochordal cells and by small chondrocyte-like cells [13]. However, by the second decade of life, the notochordal cells in the NP disappear, and the NP transitions from a notochordal structure to a tissue embedded with small chondrocyte-like cells [14].…”
Section: The Development Of the Ivdmentioning
confidence: 99%
“…Some scholars have found that human notochord cells gradually reduce with the growth of age and disc degeneration, this notochord cells are NPMSCs [17]. Rodrigues-pinto R et al found that keratin 8, 18, 19 (KRT8, KRT18, KRT19) are speci c markers of human notochord cells, and are expressed in all stages of notochord cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that species‐specific responses can be observed and as such, caution must be applied when using nonhuman cells in initial proof of principle testing. These differences could arise from differential species‐dependent expression of proteins and receptors, cell types isolated from tissues (eg, notochordal cells), or the disease status of the tissues . In view of the challenges in accessing human cells, the majority of animal cells utilized in initial experimental studies are from normal young adult animals, which do not represent the cellular phenotype seen within the degenerated (human) IVD, which are senescent and exhibit a catabolic phenotype which has implications on regenerative therapies .…”
Section: Bench Side Testing: In Vitro and Ex Vivo Testingmentioning
confidence: 99%
“…These differences could arise from differential species-dependent expression of proteins and receptors, cell types isolated from tissues (eg, notochordal cells), or the disease status of the tissues. [9][10][11] In view of the challenges in accessing human cells, the majority of animal cells utilized in initial experimental studies are from normal young adult animals, which do not represent the cellular phenotype seen within the degenerated (human) IVD, which are senescent and exhibit a catabolic phenotype which has implications on regenerative therapies. [12][13][14] Over the last 10 years, there has been increased research on human cell sources with approximately 50% of studies culturing IVD cells or cells for regeneration of the IVD sourced from human (Figure 2A,C).…”
Section: Species and Cell/tissue Sourcementioning
confidence: 99%